Angell, The Behavior of Money - Bradford, Frederick A.; Angell, James W. (Quarterly Journal of Economics, 1937)
Journal Article Angell, the Behavior of Money Get access Frederick A. Bradford Frederick A. Bradford Lehigh University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 51, Issue 2, February 1937, Pages 364–373, https://doi.org/10.2307/1882095 Published: 01 February 1937